if we divide 60 into say hmmm two integers, and those integers are say "a" and "b", then a + b = 60, therefore, a = 60 - b.
[tex]\bf \stackrel{\textit{one part is divided by 6}}{\cfrac{a}{6}}~~+~~\stackrel{\textit{the other part is divided by 8}}{\cfrac{b}{8}}~~=~~9
\\\\\\
\cfrac{60-b}{6}~~+~~\cfrac{b}{8}=9\impliedby
\begin{array}{llll}
\textit{let's multiply both sides by}\\
\textit{the LCD of 24}
\end{array}
\\\\\\
24\left( \cfrac{60-b}{6}~~+~~\cfrac{b}{8} \right)=24(9)\implies 240-4b+3b=216
\\\\\\
-b=-24\implies b=\cfrac{-24}{-1}\implies b=24[/tex]
what's the first integer? well, a = 60 - b.